Fluorine and Lithium: Ideal Partners for High‐Performance Rechargeable Battery Electrolytes. Issue 45 (24th July 2019) - von Aspern, N.; Röschenthaler, G.‐V.; Winter, M.; Cekic‐Laskovic, I.
Abstract: Further enhancement in the energy densities of rechargeable lithium batteries calls for novel cell chemistry with advanced electrode materials that are compatible with suitable electrolytes without compromising the overall performance and safety, especially when considering high‐voltage applications. Significant advancements in cell chemistry based on traditional organic carbonate‐based electrolytes may be successfully achieved by introducing fluorine into the salt, solvent/cosolvent, or functional additive structure. The combination of the benefits from different constituents enables optimization of the electrolyte and battery chemistry toward specific, targeted applications. This Review aims to highlight key research activities and technical developments of fluorine‐based materials for aprotic non‐aqueous solvent‐based electrolytes and their components along with the related ongoing scientific challenges and limitations. Ionic liquid‐based electrolytes containing fluorine will not be considered in this Review. Abstract : Opposites attract and complement : Lithium and fluorine are long‐term partners in energy storage systems, especially in Li‐based battery technologies, as they enable further improvements in energy and power density as well as enhancing life span and safety. This Review discusses key research and technical developments for the broad application of F‐based materials for liquid electrolytes in Li‐based batteries as well as related ongoing scientific challenges.